PENGARUH PENGETAHUAN WAJIB PAJAK, KESADARAN WAJIB PAJAK DAN MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (STUDI KASUS PADA WAJIB PAJAK KENDARAAN BERMOTOR YANG TERDAFTAR DI SAMSAT KOTA DEPOK 1) - Putri, Amelia Mutiara; Rosyati, Tati (Publika Citra Media, 2025)
This study aims to analyze the effect of taxpayer knowledge, taxpayer awareness and modernization of the tax administration system on motor vehicle taxpayer compliance. The population in this study were motor vehicle taxpayers registered at Samsat Kota Depok 1 totaling 1,032,932 taxpayers. The research sample used a simple random sampling technique and was determined using the slovin formula of 100 people. Based on the partial results, taxpayer knowledge has no significant effect on motor vehicle taxpayer compliance, while taxpayer awareness has a positive and significant effect on motor vehicle taxpayer compliance, and modernization of the tax administration system has a positive and significant effect on motor vehicle taxpayer compliance. Based on the simultaneous results, taxpayer knowledge, taxpayer awareness, and modernization of the tax administration system have a positive and significant effect on motor vehicle taxpayer compliance.